Neuspešno primarno zdravljenje zloma petnice - Andoljšek, Matej (Zdravniški vestnik, 2008)
Many patients are seriously disabled after failed primary treatment of calcaneal fracture. They complain about pain, swelling of the foot and ankle, stiffness and/or limping. They have problems with walking the uneven ground, standing on their toes or climbing ladders. Complains are related to injuries of the soft tissues (not discussed in this paper) and/or injures of the bones and joints. A decreased Boehler's angle resulting in flatfoot is not always aserious defect, and most patients with decreased Boehler angle do well, if there is no subtalar arthrosis and/or deformity of the calcaneus. Severe disability is mainly related to subtalar arthrosis, mechanical malalignment and impingement (lateralfibulotalar, anterior- tibiotalar). Any discongruity of the subtalar joint will end in arthrosis of subtalar joint. However, arthrosis is possible even after complete restoration of the subtalar joint due to primary cartilage injury. When conservative treatment fails, operative treatment is indicated in most patients with bone and joint problems. The goals o f surgical treatment are pain relief and restoration of talocalcaneal alignment. In lateral impingement, when subtalar joint and general alignrnent of the tuber are preserved, removal of the bulged lateral wall could suffice. In such cases a corrective osteotomy of the tuber is rarely indicated. In painfull subtalar arthrosis fusion is the only option. Limited fusion is preferable. In situ subtalar, fusion is advisable in cases without malalignment or deformity. When we have arthrosis and varus/valgus deformity with preserved height arthrodesis with corrective osteotomy is indicated. In most cases, where complex deformity is present, corrective subtalar distraction bone-block arthrodesis should be done.
Keywords: Arthrodesis; Artrodeza; Calcaneus; Fracture Fixation; Fractures; Injuries; Kalkaneus; Osteotomija; Osteotomy; petnica; therapy; zapleti; zdravljenje; Zlom, fiksacija; Zlomi